IMPLEMENTATION OF THE ELDERLY FEEDING PROGRAM IN SURABAYA (Study in Rungkut Kidul, Rungkut, Surabaya) - Eno Putri Larasati; Diana Hertati (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2021)
Surabaya is the city with the most populous population in East Java. With such a large number, population problems are unavoidable. The increasing number of the elderly is a subject that the government is currently paying special attention to. To ensure the wellbeing of the elderly, the government, together with the Social Service, took steps through the establishment of a feeding program for the destitute and abandoned elderly. This study aims to determine the implementation of the feeding program for the destitute and abandoned elderly in Rungkut Kidul. The type of research used is qualitative research. The results showed that the implementation of the elderly feeding program was in accordance with government regulations and was given to elderly beneficiaries. This study concludes that the implementation of the program is running well but not yet optimal.